WAKTU POTENSIAL APLIKASI MIKORIZA DAN Trichoderma spp. UNTUK MENINGKATKAN PERTUMBUHAN SEMAI Acacia mangium - Pratama, Rino Eka; Oktorini, Yossi; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Acacia mangium is a comodity of plantation industry that has been developed. To get a good quality of Acacia mangium must use proper cultivation techniques. Mycorrhizae and Trichoderma spp. can improve seedling growth and suppresses pathogenic soil, but need to know the potential time to apply. This research aim to know the potential application of mycorrhizal time and Trichoderma spp. to increase seedling growth. This research used a completely randomized design (CRD), which consists of 4 treatments, 5 replications and each replication consisted of 10 seedlings. The treatments used were T1 = Trichoderma spp. the S-3 and mycorrhiza on S-1, T2 = Trichoderma spp. the S-1 and S-3 mycorrhiza on, T3 = Trichoderma spp. and mycorrhiza on the S-3, T4 = Trichoderma spp. and mycorrhiza on the S-1, where S = the seedlings were transferred to polybags. Responses were measured to observe the effect of the lived seedlings, height of seedling, diameter of seedlings, plant dry weight and the ratio of the crown / root. The results of this research shows that the application of Trichoderma spp. in three days before weaning and mycorrhiza in one day before weaning tend to show better results in the growth of Acacia mangium seedlings. Keywords: Acacia mangium, Mycorrhizae, Trichoderma spp., potential time.